The Microstructure and Cutting Property of CrAlN Nanocomposite Coating - WANG Xin, FAN Qi - xiang, WANG Tie - gang, CAO Feng - ting, LUO Zhong - hong (Cailiao Baohu, 2021)
The previous studies of CrAlN nanocomposite coating are mainly focused on the structure, mechanical performance, high - temperature oxidation resistance, but there are few reports on the cutting property of coatings. In this work, a CrAlN nanocomposite coating was deposited by arc ion plating and pulsed DC magnetron sputtering co - deposition technology, and the microstructure and mechanical property of the coating were studied by means of X - ray diffraction (XRD), scanning electron microscopy (SEM), nano - indentation and scratch tester. Results showed that the CrAlN nanocomposite coating was composed of fcc - (Cr,Al)N phase mainly and a few hcp - AlN phase, and the preferential orientation of CrAlN nanocomposite coating was the (111) crystal plane. Owing to the solid solution strengthening effect of Al element, the hardness of CrAlN coating reached the value of 31.9 GPa. The coating was well adhesive to the substrate, and the highest critical load was up to 85.6 N. Moreover, the cutting property of CrAlN nancomposite coating was tested by cutting 45 steel, and a thermal imager was used to measure the temperature of cutting zone. The test result showed that the cutting time of the CrAlN nanocomposite coating was 3 times longer than that of uncoated cutting tool when the cutting width of tool flank reached 0.3 mm, which was used as blunt standard. In addition, the CrAlN nanocomposite coating possessed lower cutting temperature than uncoated cutting tool during the cutting process. This might be contributed to that in CrAlN nanocomposite coating, Al was soluble in the CrN lattice, and the hardness of the CrAlN coating was improved by solution strengthening effect, which endowed the CrAlN nanocomposite coating with higher wear resistance, lower the friction coefficient and longer tool service life.